Investigation and analysis on the current status of single-arm clinical trial with external control - Jia-Ning LIU; Ming-Yuan CAI; Lin-Bo LU; Jin-Hua SI; Ge LI; Feng SUN (Yixue xinzhi zazhi)
Objective To study the progress of single-arm trials with external controls using bib-liometric methods and compare Chinese and foreign literature to understand research directions and trends.Methods We performed computer searches of five databases (PubMed, SinoMed, CNKI, Wan-fang and VIP) and obtained all single-arm trials with external controls published before July 21, 2021. Reviewers screened the literature and extracted data independently. The CiteSpace and VOSviewer were used for bibliometric analysis.Results A total of 67 articles were included, of which 56 were in English and 11 in Chinese. The first literature included was published in 1997, The highest number of published papers was in 2017(14.93%). These articles were mainly about drug therapy (59.70%) and medical devices (23.88%).Confounding factors were controlled in a few literatures (37.31%), including matching and statistical analysis. Target diseases mainly focus on oncology (35.82%) and circulatory diseases (25.33%). The main disease fields are circulatory system diseases in Chinese papers and on-cology and circulatory system diseases in English ones. Most studies used historical controls (82.09%). The majority of the studies were in phase Ⅱ and evaluated safety (68.66%) and efficacy (94.03%).Conclusions Single-arm trials with external controls often use historical controls, and play an important role in the fields of rare diseases, refractory diseases and other situations where it is difficult to set con-trol groups. There are some differences between China and other countries; however, we both have a long way to go.